INTERNATIONAL TRADE AND GENDER WAGE GAP IN CHINA - Wei, Hao; Yang, Sui; Liu, Shibin; Wu, Jun; Xiang, Songlin (European Scientific Journal, ESJ, 2013)
It is a new field to analyze how foreign trade impacts gender wage gap in China. Combining Chinese Household Income Project (CHIP) in 2002 and 2007, the paper aims at researching the impacts of international trade on gender wage discrimination. The paper finds that the development of foreign trade will increase gender wage inequality, which contradicts the neoclassical theory. Specifically, in the aspect of trade dependence, the import dependence and total trade dependence has a statistically significant and positive impact on gender wage gap. From the perspective of mode of trade, compared with processing trade dependency, the import dependency of general trade and foreign trade dependency have more statistically significant impacts on gender wage gap, and the impact of import of general trade on gender wage gap is sizable and statistically significant. From the perspective price, price of trade has a negative impact on gender wage gap, but compared with the price changes of total trade and processing trade, only import price of general trade and total price of import and export have statistically significant impacts on gender wage gap. Finally, changes of terms of trade have a positive impact on gender wage gap, but the impact is not statistically significant.